Benedito Calixto com influência criativa - Fernandes, Leonardo Bonfim [UNESP] (2017)
It presents the research project aiming at the realization of a painting inspired by the works of Benedito Calixto, in view of analyzes photographic records and studies of the elements present in his paintings. The purpose of this study is to preserve the painter's memory through bibliographical surveys and the elaboration of an instructive pictorial project